FRENCH ENVIRONMNETAL SOCIOLOGY FACING INTERDISCIPLINARY RESEARCH ACROSS SOCIAL AND NATURAL SCIENCES - Aspe Chantal; Jacque Marie (European Scientific Journal, ESJ, 2013)
Interdisciplinary research between social and natural sciences appear both as constitutive of environmental sociology and the main problem for its disciplinary and institutional recognition. Interdisciplinary research programs are widely acknowledged in the environmental field, particularly due to their linkage with social demand. Conversely, researchers embarked in this practice are often perceived as marginal from their discipline’s standpoint. Based on the French experience, this paper shows how interdisciplinary research plays a reflexive role for environmental sociology by theorizing the “co-construction” of ecological and social systems. Interdisciplinarity is not a purpose for environmental sociology but a necessary approach to confront its theoretical breakthroughs and the social and political understanding of the environmental issue to the ecological reality.